Spatial and Textural Aspects for Arabic Handwritten Characters Recognition - Boulid, Youssef; Souhar, Abdelghani; Ouagague, Mly. (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2022)
The purpose of the present paper is the recognition of handwritten Arabic characters in their isolated form. The specificity of Arabic characters is taken into consideration, each of the proposed feature extraction method integrates one of the two aspects: spatial and textural. In the first step, a modified Bitmap Sampling method is proposed, which converts the character’s images into a binary Matrix and then constructs a Mask for each class. A matching rate is used between the input binary matrix and the masks to determinate the corresponding class. In the second step we investigate the use of an Artificial Neural Network as classifier with the binary matrices as features and then the histograms of Local Binary Patterns to capture the texture aspect of the characters. Finally, the results of these two methods are combined to take into consideration both aspects at the same time. Tested on the Arabic set of the Isolated Farsi Handwritten Character Database, the proposed method has 2.82% error rate.
Keywords: arabic documents; handwritten character recognition; local binary patterns; modified bitmap sampling; IJIMAI